The effect of retention control training in the treatment for primary nocturnal enuresis - Tojyo, M.; Madeda, K. (Japanese Journal of Behavior Therapy, 1991)
The purpose of this study is to examine the effect of Retantion Control Training with a limited number of four times a day in the treatment for primary nocturnal enuresis. Four clients who satisfied the following conditions : (1)over 6 years old, (2)having no organic abnormalites, (3)who were suffering from primary nocturnal enuresis, (4)with no mental retardation were chosen as training subject. They were divided into two conditions. One condition of 2 clients was induced into traininig immediately after base line measurement (T group) The other condition of also 2 clients (WL group) underwent a four week control period before the training. And this time, after two week base line measurement, the regular type of Retention Control Training was conducted on 2 clients who have mental retardation and who were the comparison group (C group). After the treatment, the client in the T group and WL group got rid of their enuresis, and there was no recurrence within a three years follow up period. However, the symptom was not totally removed in group C althOLlgh some improvement was seen. The result of the training show that Retention Control Training works effectively on clients who satisfy the above conditions even with limited number of trainings. Plus the results suggest that positive effect could be expected in the case of clients with mental retardation when Retention Control Training and another method such' as Dry-Bed Training are used concurrently.